ESIPT and FRET probes for monitoring nanoparticle polymer coating stability. Issue 25 (14th June 2017) - Azcárate, Julio. C.; Díaz, Sebastián A.; Fauerbach, Jonathan A.; Gillanders, Florencia; Rubert, Aldo A.; Jares-Erijman, Elizabeth A.; Jovin, Thomas M.; Fonticelli, Mariano H.
Abstract : Coating strategies of inorganic nanoparticles (NPs) can provide properties unavailable to the NP core alone, such as targeting, specific sensing, and increased biocompatibility. Abstract : Coating strategies of inorganic nanoparticles (NPs) can provide properties unavailable to the NP core alone, such as targeting, specific sensing, and increased biocompatibility. Non-covalent amphiphilic NP capping polymers function via hydrophobic interactions with surface ligands and are extensively used to transfer NPs to aqueous media. For applications of coated NPs as actuators (sensors, markers, or for drug delivery) in a complex environment, such as biological systems, it is important to achieve a deep understanding of the factors affecting coating stability and behavior. We have designed a system that tests the coating stability of amphiphilic polymers through a simple fluorescent readout using either polarity sensing ESIPT (excited state intramolecular proton transfer) dyes or NP FRET (Förster resonance energy transfer). The stability of the coating was determined in response to changes in polarity, pH and ionic strength in the medium. Using the ESIPT system we observed linear changes in signal up to ∼20–25% v/v of co-solvent addition, constituting a break point. Based on such data, we propose a model for coating instability and the important adjustable parameters, such as the electrical charge distribution. FRET data provided confirmatory evidence for the model. The ESIPT dyes and FRET based methods represent new, simple tools for testing NP coating stability in complex environments.